(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2008)
The present paper aims to show that, based on an analysis of the notion of “behavior of the listener” in Skinner’s work, the claim that the behavior of the listener is not verbal is inconsistent with the definiton of verbal behavior. Following the results of such conceptual analysis, some considerations are made on Skinner’s revision of the behavior of the listener. Also presented are some alternative approaches for the study of verbal behavior, in which the behavior of the listener seems to have received a treatment more coherent with its importance for the verbal episode. The discussion presented here seeks to encourage a more critical use of the terminology proposed by Skinner, based on the realization that any inconsistence in the conceptual treatment of a given phenomenon will inevitably lead to inconsistency in every level of the scientific enterprise related to that phenomenon.